Severe neonatal cholestasis in HNF1β deficiency: a case report and literature review - Gagliano, Chiara; Burattini, Olga; Paradisi, Luigi; Recchione, Sarah; Santoro, Lucia; Caponi, Laura; Ciaschini, Annamaria; Lionetti, Maria Elena; Gatti, Simona (Frontiers in Pediatrics, 2025)
Neonatal cholestasis can be caused by several conditions, with biliary atresia being the major cause. Genetic and endocrinological etiologies represent other possibilities, with most of them requiring a rapid diagnosis and a specific treatment. We describe a neonatal case of severe cholestasis with low gamma glutamyl transferase in a child presenting with multiple abnormalities, including pituitary stalk interruption syndrome and consequent hypopituitarism. The cholestasis was rapidly resolved with hormone therapy. Genetic analysis showed a de novo 17q chromosome deletion, including the HNF1β gene implicated in liver damage, and this was considered causative of the complex clinical phenotype. Our case highlights the relationship between congenital hypopituitarism and HNF1β gene deletion in 17q12 deletion syndrome as a severe neonatal cholestasis etiology, emphasizing the need to be especially vigilant in cases with associated hypoglycemia. Prompt endocrine evaluation and genetic testing are crucial in neonatal cholestasis to start targeted therapy and long-term monitoring, which could mitigate serious complications.